Differences of Atocion lithuanicum from A. armeria and their hybrid (Sileneae, Caryophyllaceae) by ITS1-ITS2 sequences and secondary structure of their transcripts - Martyniuk, V.O.; Karpenko, N.I.; Tarieiev, A.S.; Kastikov, I.Yu. (Український ботанічний журнал, 2018)
Many plant species have controversial taxonomical status, and clarification of that status is extremely important in cases of rare taxa when the need for their conservation is discussed. One of them is Atocion lithuanicum – an endemic taxon, treated either as separate species or synonym of A. armeria. The aim of the present study is to infer the taxonomic status of A. lithuanicum, using molecular phylogenetic analysis as well as ITS1 and ITS2 secondary structures comparison of those two taxa and their putative hybrid. The results of our phylogenetic analysis using Bayesian inference reveal that A. lithuanicum is not closely related to A. armeria, but instead is sister to A. compactum. However, phylogenetic relationships on the tree, which includes hybrids and taxa with SNPs, are not resolved well. In contrast, ITS1 secondary structure analysis allows us to distinguish clearly A. lithuanicum from A. armeria. The artificial F1 hybrid between these species has SNPs in all sites that differentiate parental forms and, by secondary structure, are located in the intermediate position between them. Thus, SNPs do not seem to be useful in phylogenetic analysis in this case. At the same time, ITS1 and ITS2 secondary structure reconstruction with SNP sites could be used as markers of hybridization events. Atocion lithuanicum is considered as separate species and could not be treated as synonym or variety of A. armeria.